Penatalaksanaan Fisioterapi Pada Kondisi Keterbatasan Luas Gerak Sendi Lutut Post Total Knee Replacement Dextra Di RSUD Panembahan Senopati Bantul - Kusumaningrum, Wuri; , Dwi Rosella Komala Sari, S.Fis, M.Fis (2015)
Background: Total Knee Replacement or TKR surgery orthopedic surgery is performed to replace the cartilage cushioning the knee joint with an artificial cushion contained iron. TKR actions performed when the knee joint damage is severe and as the final solution when the use of knee braces and treatment is no longer effective. TKR action is usually done at age ≥70 years but the proportion of younger patients undergoing TKR increased significantly. Objective: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion, reduction of edema and increased functional activity using Transcutaneus modalities Electrical Nerve Stimulation (TENS) and therapeutic exercises such as static contraction and hold relax. Results: After treatment six times therapy showed a decrease in pain of movement, a vast increase of motion, decrease edema, and an increase in functional ability, especially when the activity up and down the stairs 3 trap, functional ability exertional sitting to standing and walking 15 meters yet changes. Conclusion: After physiotherapy intervention using modalities such as Transcutaneus Electrical Nerve Stimulation (TENS) and exercise therapy on the condition of motion of joints Knee Size Limitations Post Total Knee Replacement Dextra, obtained a decrease pain, increase range of motion, and decrease edema, so as to improve the ability of functional.